2015
DOI: 10.1116/1.4922646
|View full text |Cite
|
Sign up to set email alerts
|

Burr-like, laser-made 3D microscaffolds for tissue spheroid encagement

Abstract: The modeling, fabrication, cell loading, and mechanical and in vitro biological testing of biomimetic, interlockable, laser-made, concentric 3D scaffolds are presented. The scaffolds are made by multiphoton polymerization of an organic-inorganic zirconium silicate. Their mechanical properties are theoretically modeled using finite elements analysis and experimentally measured using a Microsquisher(®). They are subsequently loaded with preosteoblastic cells, which remain live after 24 and 72 h. The interlockabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Polymerization or decomposition occurs only at the focal spot of a pulse laser, where the intensity of the absorbed light is the highest, 3D microstructures are then achieved after the development in a solvent. TPF is an outstanding 3D nanoscale manufacturing tool that offers great potential for rapid prototyping, and the manufacture of photonic devices, tissue scaffolds, biomedical parts, and microdevices . Among the various 3D microfabrication techniques, such as layer by layer microfabrication, electrodeposition, nanoimprint, and multibeam interference lithography, TPF is the most powerful method by moving the focused beam in photoresist according to a computer‐designed 3D route with a resolution beyond the optical diffraction limit, for complex 3D microstructure preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization or decomposition occurs only at the focal spot of a pulse laser, where the intensity of the absorbed light is the highest, 3D microstructures are then achieved after the development in a solvent. TPF is an outstanding 3D nanoscale manufacturing tool that offers great potential for rapid prototyping, and the manufacture of photonic devices, tissue scaffolds, biomedical parts, and microdevices . Among the various 3D microfabrication techniques, such as layer by layer microfabrication, electrodeposition, nanoimprint, and multibeam interference lithography, TPF is the most powerful method by moving the focused beam in photoresist according to a computer‐designed 3D route with a resolution beyond the optical diffraction limit, for complex 3D microstructure preparation.…”
Section: Introductionmentioning
confidence: 99%
“…However, our focus was to compare both experimental conditions (spheroids in the absence or into lockyballs). Our previous study [18] also reported an efficient cellularization with a considerable cell viability using a pre-osteoblastic lineage into lockyballs. In this study, beyond cellularization and viability parameters, we showed maintenance in ASCs differentiation potential for chondrogenic and osteogenic lineages by gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Danilevicius et al [18] showed an efficient cellularization of lockyballs using a mouse calvaria preosteoblastic cell line. However, the main limitation of this study relies on cell type, since cell lineages from mouse origin are not appropriate for clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…A number of innovative tissue-engineered methods to fabricate biomimetic Ewing's sarcoma tumors have been highlighted, emphasizing the role of the extracellular matrix and the surrounding cellular milieu and suggesting potential applications to improve our understanding of similar tumor biology, preclinical drug testing and personalized medicine [43]. Microengineered biomimetic 3D tissue models resemble the physiological properties of native tissues, having the advantages of potential preclinical models for the development of predictive drug screening assays in specific disease models [44], whereas interlockable microscaffolds fabricated by direct laser writing provide a tailor-made architecture for the encagement of cell spheroids suitable as in vitro model in several applications [45]. By means of simple spheroid technology based on an aqueous two-phase system [46], cancer cells confined in a drop of the denser aqueous dextran phase are robotically dispensed into microwells with the aqueous polyethylene glycol phase, forming viable spheroids, without a need for any external stimuli.…”
Section: Technologies To Produce Cell Spheroidsmentioning
confidence: 99%